From vacant space to active place: leveraging state-owned land for affordable housing - a case study of Youngsfield - Parker, Megan (School of Architecture, Planning and Geomatics, 2018)
Access to affordable housing in well-located areas across Cape Town is a pressing issue faced by low-income households. Attempts have been made at addressing the issue through affordable and free housing subsidies being implemented, but these have not improved access to opportunities for low-income households. These land distribution patterns are a result of recycled apartheid policies perpetuated by an unequal urban land market that does not allow low-income groups to participate. This research focuses on the spatial fragmentation of apartheid planning and its effect on low-income households in accessing subsidised housing in well-located areas. Through the collation of a spatial development framework, this study addresses the accessibility to affordable housing for low-income households by utilising state-owned land at Youngsfield Military Base and Royal Cape Golf Course in Wetton and Ottery, suburbs bordering the southern suburbs and Cape Flats district. The research process began with a spatial analysis which outlined the metropolitan, sub-metropolitan and site context for potential affordable housing development on well-located state-owned land. This supplied a detailed context for the needs of the site, the environmental context and confirmed the good location of the study area in relation to opportunity areas. Spatial design principles were then chosen to inform the creation of a quality urban environment with high-density mixed-use affordable housing and other economic and amenity opportunities. Relevant housing policies were analysed and ample existing policies were found which address affordable housing implementation in South Africa. Unfortunately, other affordable housing options such as social housing and subsidised loan housing are happening at a slower pace than Breaking New Ground (BNG) subsidised housing. Precedents of affordable and social housing were identified, many of which have been successfully implemented, but some still lack the incorporation of essential spatial concepts that create quality urban environments in residential developments. The concept proposal plan illustrated the use of literature and key spatial concepts informing the development of the site. Essential aspects of development were calculated to facilitate thorough planning for public facilities, public transport and affordable housing implementation. The research included an implementation section which identified the relevant stakeholders who would be engaged with during the planning process and affordable housing implementation. Using the package of plans process, the site was divided into precincts to easily streamline the development of the entire site. Appropriate social housing institutes and affordable housing companies were considered as possible institutions to manage and partially fund developments. Feasibility of cross-subsidisation was considered as a major option during implementation of the long-term phasing of the development. The research and implementation illustrates that by using existing policies and appropriate stakeholders and institutions efficiently, the creation of quality urban environments for affordable housing is possible. With the proper city officials in place and the political will for the development, housing developments on this scale can provide large numbers of affordable housing opportunities in better located areas.